THE EFFECTIVENESS OF GREEN SEAWEED (Ulva reticulate) ANTIBACTERIAL COMPOUND EXTRACT ON THE BACTERIA Vibrio parahaemolyticus - Anis Zubaidah; Riza Rahman Hakim; Olivia Agustin (Universitas Mataram, 2024)
Green seaweed (Ulva reticulata) is found in many parts of Indonesia. The potential of green seaweed is not widely known to the public, even though it is considered a parasite on other types of seaweed. The purpose of this study was to determine the antibacterial compounds contained in green seaweed and their effectiveness against Vibrio parahaemolyticus bacteria. Green seaweed was extracted by maceration method and then qualitative and quantitative tests were carried out. After that, the minimum inhibitory concentration test was carried out and continued with the minimum bactericidal concentration test and the inhibition test with 5 treatments and 3 replications. The data from the qualitative and quantitative test of seaweed, the minimum inhibitory concentration and the minimum bactericidal were analyzed descriptively, while the data from the inhibition zone test was analyzed statistically by ANOVA. The results of qualitative and quantitative tests showed that green seaweed contained flavonoids (6.4909 mg/g), tannins (70.7500 mg/g) and saponins (443.7286 mg/g). The results of the minimum inhibitory concentration test showed that the concentration of 3.125% was the minimum concentration to inhibit bacterial growth. In the inhibition test, it can be seen that P4 (6%) is the best treatment. The results of statistical analysis show that the treatments given are significantly different, except that P4 (6%) and P5 (7,5%) are not significantly different. From this study it can be concluded that green seaweed extract is effective in inhibiting the growth of Vibrio parahaemolyticus bacteria.